Black Lives Matter: We are in the Same Storm but we are not in the Same Boat. Issue 4 (9th November 2020) - Watson, Marlene F.; Turner, William L.; Hines, Paulette Moore
Abstract : Black Lives Matter is a clarion call for racial equality and racial justice. With the arrival of Africans as slaves in 1619, a racial hierarchy was formed in the United States. However, slavery is commonly dismissed as that less than noble aspect of the United States' history without really confronting the legacies of racial inequality and racial injustice left in its wake. White supremacy, based on the myths of white superiority and Black inferiority, have obscured racial inequality and racial injustice, resulting in blaming the victims. Using Black Lives Matter as a platform, we focus on some key considerations for theory, research, education, training, and practice in clinical, community, and larger systems contexts. Broadly, we focus on Black Lives Matter, literally; Black dehumanization; historical oppression; healing; and implications for the field of family therapy. More specifically, we draw attention to health disparities, mass incarceration and aggressive policing, intergenerational racial trauma, restorative justice, and antiracist work. Resumen: El movimiento Black Lives Matter (Las vidas de los negros son importantes) es un llamamiento a la igualdad y la justicia racial. Con la llegada de los africanos como esclavos en el año 1619, se formó una jerarquía racial en los Estados Unidos. Sin embargo, la esclavitud generalmente se desestima como el aspecto menos noble de la historia de los Estados Unidos sin afrontar realmente los legados de desigualdad e injusticia raciales que dejó. La supremacía blanca, basada en los mitos de la superioridad blanca y la inferioridad negra, han ocultado la desigualdad y la injusticia raciales, lo cual condujo a la culpabilización de las víctimas. Utilizando el movimiento Black Lives Matter como plataforma, nos centramos en algunas consideraciones clave para la teoría, la investigación, la educación, la capacitación y la práctica en contextos clínicos, comunitarios y en sistemas más grandes. En líneas generales, nos centramos en Black Lives Matter, literalmente; en la deshumanización de los negros, la opresión histórica, la recuperación, y las consecuencias para el área de la terapia familiar. Más específicamente, visibilizamos las desigualdades sanitarias, el encarcelamiento masivo y la vigilancia policial agresiva, el trauma racial intergeneracional, la justicia reparadora y la labor antirracista. 摘要: 黑人的命也是命是种族平等和种族正义的号角。随着1619年非洲人作为奴隶来到美国, 美国形成了种族等级制度。然而, 人们通常把奴隶制当作美国历史上那不那么高尚的一面, 而没有真正正视奴隶制遗留下来的种族不平等和种族不公正。白人至上主义基于白人优越和黑人低劣的神话, 掩盖了种族不平等和种族不公正, 导致了对受害者的指责。以 "黑人命也是命 "为平台, 我们重点讨论了临床、社区和更大系统背景下理论、研究、教育、培训和实践的一些关键考虑。广义上讲, 我们关注的是 "黑人命也很重要", 从字面上看; 黑人非人化; 历史压迫; 治疗; 以及对家庭治疗领域的影响。更具体地说, 我们提请注意健康方面的差异性、大规模监禁和暴力执法、代际种族创伤、恢复性司法和反种族主义工作。